Aryl Hydrocarbon Receptor Regulates Apoptosis and Inflammation in a Murine Model of Experimental Autoimmune Uveitis - Huang, Yike; He, Junchi; Liang, Huaping; Hu, Ke; Jiang, Shaoqiu; Yang, Lu; Mei, Suyin; Zhu, Xiao; Yu, Jing; Kijlstra, Aize; Yang, Peizeng; Hou, Shengping (Frontiers in Immunology, 2018)
Uveitis is characterized as a common cause of blindness worldwide. Aryl hydrocarbon receptor (AhR), a ligand-activated nuclear receptor, has been implicated to play a role in human uveitis, although the exact mechanisms remain poorly understood. The purpose of this study was to enhance our knowledge concerning the role of AhR during intraocular inflammation. We immunized wild type and AhR knockout C57BL/6J mice with IRBP651-670 to induce experimental autoimmune uveitis (EAU). Disease severity was evaluated with both clinical and histopathological grading. Blood–retinal barrier (BRB) integrity was tested by Evans blue and tight junction proteins qualifications. Apoptosis was measured using TUNEL staining. Macrophage/microglia activation and polarization were studied by immunofluorescence and Western blot. Following EAU induction, AhR-/- mice had more severe clinical and histopathological manifestations of uveitis than AhR+/+ mice. Increased vascular permeability and apoptotic cells were observed in AhR-/- EAU mice when compared with AhR+/+ EAU mice. Additionally, AhR-/- EAU mice showed evidence of a significantly increased macrophage/microglia cells and a stronger polarization from the M2 to the M1 phenotype as compared to AhR+/+ EAU mice. The levels of pro-inflammatory cytokines including TNF-α, IL-6, IL-1β were increased in AhR-/- EAU mice, which was associated with the activation of NF-κB and STAT pathways. 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), an agonist of AhR, caused a significant decrease in the clinical and histopathological manifestations, preserved blood–retinal barrier (BRB) integrity, reduced apoptotic cells, inhibited macrophage/microglia activation and shifted their polarization from M1 towards M2. Moreover, decreased expression of pro-inflammatory cytokines including TNF-α, IL-6, IL-1β and inhibition of NF-κB and STAT pathways were found in EAU mice following TCDD treatment. In conclusion, AhR activation with TCDD exhibits an immunomodulatory effect by reducing BRB breakdown, inhibiting retinal cell apoptosis, and reducing pro-inflammatory cytokine expression during EAU. The underlying mechanism may involve the modulation of macrophages/microglia polarization and the down-regulation of NF-κB and STAT pathways.